SINERGITAS PEMERINTAH DALAM PENANGANAN KONFLIK BATAS WILAYAH ANTARA KABUPATEN LOMBOK BARAT DAN KABUPATEN LOMBOK TENGAH - ayumei ameiranda; Syamsunasir Syamsunasir; Achmed Sukendro; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The territorial boundary conflict between West Lombok and Central Lombok districts in West Nusa Tenggara (NTB) province has been going on for several years, with various attempts being made to find an appropriate solution. This study aims to analyze the synergies carried out by the Provincial Government of NTB in handling boundary conflicts. The research method used is a case study with in-depth interviews with informants involved in handling boundary conflicts. The results of the study show that government synergy in resolving boundary conflicts involves the West Lombok Regency Government, Central Lombok Regency Government, community leaders, and other relevant agencies. The synergies carried out include facilitating meetings, strengthening the authority of the Border Dispute Resolution Team so that it has a large and strong capacity, approaching the community, coordinating the central government with local governments regarding border conflicts between Central Lombok and West Lombok Regencies by providing coordination space. The governor acts as the representative of the central government in the province, so that the central government is under the command of the provincial government. The results of this research are the Decision of the Supreme Court of the Republic of Indonesia Number 1 P/Hum/2023 dated 9 February 2023, in the case submitted by the Regent of Central Lombok as the applicant party and the Minister of Home Affairs as the respondent. It has been decided that Nambung will become part of Central Lombok Regency.